Influence Of Drop Size Distribution And Kinetic Energy In Laboratory Rainfall Simulation - Roshar, Mohamad Syarees (Universiti Sains Malaysia, 2022)
Numerous scientific evidence has given credence to the true existence and deleterious impacts of climate change on slope. Different means of hydrological data collection have developed and used to replicate the natural rainfall on laboratory scale model even though it is difficult. The aim of this paper was to use a drip-type rainfall simulator to design, build, calibrate, and run a simulated rainfall. Rainfall intensities of 60 and 80 mm/h were used to represent heavy rainfall events of one hour duration. Flour pellet methods and sieve analysis were used to obtain the drop size distribution of the simulated rainfall. The results show that the average drop size for all investigated rainfall intensities ranging from 4 - 5 mm. The median value of the drop size distribution or known as D50 of simulated rainfall for 60 and 80 mm/h are 4.03 and 5.12 mm, respectively. Due to the comparatively low drop height of 2.3 m, the terminal velocities monitored were between 75% which is 8.82 for 60 mm/hr and 9.11 for 80 mm/hr, were lower than the value for natural rainfall with more than 90% for terminal velocities. This condition also reduces rainfall kinetic energy of 27.42- 28.51 J/m2mm compared to natural rainfall. This also contribute to small mass movement of soil because there is no significant change in slope surface during simulation. This phenomenon, which represents the best interchange between all pertinent rainfall parameters found with the particular simulator setup, is relatively prevalent in portable rainfall simulators. The unpredictable and erratic changeability of natural rainfall is eliminated because rainfall may be regulated. The main focus is on drip-type rainfall simulators, which produce properties of rainfall that are almost identical to those of actual rainfall.